Chemometric techniques for quantitative analysis - Kramer, Richard, 1953- (Marcel Dekker, 1998)
Shows how to produce and use quantitative analytical calibrations in a laboratory or production environment, how to estimate the time and resources needed to develop analytical calibrations, and how to employ the quantitative software provided with a range of instruments and software packages.